2021
DOI: 10.3390/jof7020125
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Gene Silencing in Fungi Using Genetically Engineered Bacteria

Abstract: Exploiting RNA interference (RNAi) in disease control through non-transformative methods that overcome the hurdle of producing transgenic plants has attracted much attention over the last years. Here, we explored such a method and used non-pathogenic bacteria as a versatile system for delivering RNAi to fungi. Specifically, the RNaseIII-null mutant strain of Escherichia coli HT115(DE3) was transformed with two plasmid vectors that enabled the constitutive or IPTG-inducible production of double-stranded RNAs (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…SIGS constitutes an environmentally friendly approach for the control of fungal plant diseases. However, its commercial application is still limited due to the instability of dsRNA under field conditions (Cagliari et al, 2019; Dalakouras et al, 2020; Niño‐Sánchez et al, 2021). This work investigated using LDH as an RNA carrier, extending on previous studies which have shown that LDH‐bound dsRNA is protected from environmental degradation (Mitter et al, 2017; Jain et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…SIGS constitutes an environmentally friendly approach for the control of fungal plant diseases. However, its commercial application is still limited due to the instability of dsRNA under field conditions (Cagliari et al, 2019; Dalakouras et al, 2020; Niño‐Sánchez et al, 2021). This work investigated using LDH as an RNA carrier, extending on previous studies which have shown that LDH‐bound dsRNA is protected from environmental degradation (Mitter et al, 2017; Jain et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inorganic and organic carriers, another delivery method being investigated is the use of vectors that have been genetically modified to produce dsRNAs. Niño-Sánchez et al first demonstrated that silencing can be induced by the application of living or lysed bacteria engineered to produce biologically active dsRNAs targeting fungal genes [ 215 ]. Further development and improvement of methods to minimize the degradation of dsRNA molecules and to improve their stability and durability are needed to allow this SIGS to be used in the field.…”
Section: Rna Interference (Rnai): the Targeted Management For Plant D...mentioning
confidence: 99%
“…Thus, large quantities of dsRNA can be produced with bacteria-based systems at a cost-effective price. Moreover, the application of living dsRNA-producing bacteria for gene silencing has been used in nematodes [ 160 ], insects [ 225 ], crustaceans [ 226 ], mammalian cells [ 227 ], and filamentous fungi [ 215 ]. However, in order to avoid bacterial release into the environment, it is necessary to purify the RNA, which can make the process more expensive and limit the amount of dsRNAs produced [ 26 , 228 , 229 , 230 , 231 , 232 ].…”
Section: Rna Interference (Rnai): the Targeted Management For Plant D...mentioning
confidence: 99%
“…Foliar sprays, trunk injections, root drench, or delivery from clay granules can also be used for sustained release of dsRNA ( Ghosh et al, 2018 ). Another promising approach, exemplified in some of the studies described below, is to use transgenic bacteria as a source of sRNA ( Niño-Sánchez et al, 2021 ).…”
Section: Spray-induced Gene Silencingmentioning
confidence: 99%